The Shaker village - Bial, Raymond; Bial, Raymond (Lexington, Ky. : University Press of Kentucky, 2008)
Photographed at the Shaker Village of Pleasant Hill, Kentucky, this volume introduces the traditional Shaker way of life in text and full-color photographs. The text describes the people as they lived, worked, and changed as well as the origins of the sect, their beliefs, activities, clothing, inventiveness, skills, and humanity. The author explains the Shaker ideal of functional simplicity, through descriptions of their mode of life, and devotion to productive work. This book is an introduction to the history and philosophy of the United Society of Believers in Christ's Second Appearing, commonly known as the Shakers.
Rev. ed. of: Shaker home. 1994.
Includes bibliographical references (p. 36-38).
Description based on print version record.
Keywords: Shakers -- United States -- Juvenile literature; JUVENILE NONFICTION / General; Electronic books